2011
DOI: 10.1016/j.cub.2010.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Variability in PI3K Protein Level Regulates PI3K-AKT Pathway Activity in Cell Populations

Abstract: Summary Background Cell-to-cell variability in populations has been widely observed in mammalian cells. This heterogeneity can result from random stochastic events or can be deliberately maintained through regulatory processes. In the latter case, heterogeneity should confer a selective advantage that benefits the entire population. Results Using multicolor flow cytometry, we have uncovered robust heterogeneity in PI3K activity in MCF10A cell populations, which had been previously masked by techniques that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 39 publications
7
86
1
Order By: Relevance
“…We detected increased PI3K signaling in each of the PI3K-H1047R mutant engineered cell lines grown in spheroid culture, as assessed by Western blot analysis of serine 473 of the downstream effector protein AKT ( Fig. 2A and B), similar to previous reports (20,(29)(30)(31)(32)(33). In addition, we observed an increase in phosphorylated S6 ribosomal protein, which lies downstream of AKT (Supplementary Fig.…”
Section: Pi3k Wt and Mutant Engineered Cells Exhibit A Range Of Resposupporting
confidence: 75%
“…We detected increased PI3K signaling in each of the PI3K-H1047R mutant engineered cell lines grown in spheroid culture, as assessed by Western blot analysis of serine 473 of the downstream effector protein AKT ( Fig. 2A and B), similar to previous reports (20,(29)(30)(31)(32)(33). In addition, we observed an increase in phosphorylated S6 ribosomal protein, which lies downstream of AKT (Supplementary Fig.…”
Section: Pi3k Wt and Mutant Engineered Cells Exhibit A Range Of Resposupporting
confidence: 75%
“…Chen et al (2005) have shown that, in mouse models of prostate cancer, loss of PTEN drives cells into senescence. Yuan et al (2011) have shown data indicating that high levels of PI-3-kinase activity can drive breast epithelial cells into senescence. These differences may be a reflection of the striking tissuespecific effects of relatively small changes in signaling through the PI-3-kinase pathway (Carracedo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent work shows that dephosphorylation of the p110-free p85␤ regulatory subunit leads to its degradation through F-box protein FBXL2 (12). Importantly, the catalytic subunit PIK3CA may also be subject to a similar regulation: that is, a dynamic cycle of proteasomedependent degradation and resynthesis of PIK3CA was observed in response to the stimulation of epidermal growth factor (13).…”
mentioning
confidence: 99%